Under the same sky: everyday politics of religious difference in southern Turkey - Daǧtaș, Seçil (University of Pennsylvania Press, 2025)
"This book examines the everyday lives of religious minorities near Turkey's border with Syria, showing how their shared social spaces sustain and transform religious differences. The book offers a nuanced perspective on secularism, religious plurality, and interfaith relations in the Middle East, moving beyond identity-based politics and analyses"-- Provided by publisher